Determination of metal content and an assessment of potential use of waste cashew nut ash (CNAS) as a source for potash production. (2011)
The potential use of waste cashew nut shell (CNS) ash as a source for potash production was investigated in this study. Managing waste ash generated from cashew nut processing is a major challenge, as land filling and open dumping of the waste ashes have been the main options in management of the ash in Nigeria. Economically viable ways of using waste ash rather than having to dispose of it have to be investigated. The CNS was air-dried for 4 weeks and combusted to ashes; the resulting ash was extracted with water for its potash content. Some parameters of the CNS, including moisture, dry matter, and ash content, were determined. Potash yield obtained was 33.4% of 150 g CNS ash used; analysis of the potash gave it a percentage purity of 78%, while purity on recrystalization increased to 86%. Potash yield from CNS ash was comparable to those reported for wood ash, plantain peels, and other agro-wastes. Also, the results showed that the CNS shared similar lignocellulosic properties and characteristics with hardwood biomass